Subsidy Shock and Social Vulnerability: Socioeconomic Effects of Fuel Subsidy Removal in Northern Nigeria - Usman Sambo; Kachalla Bura Lumami (Pen of Social Science, 2026)
The fuel subsidy had previously served as a silent form of social protection in Nigeria, shielding vulnerable groups from high living costs in a country where poverty is widespread and social welfare is lacking. The financial burden of subsidising fuel, combined with perceptions of poor performance, sustained ongoing debate about whether to remove the subsidies. In 2023, the Nigerian government abruptly decided to remove fuel subsidies, leading to a significant increase in food, energy, and transportation costs. This research will assess the broader socioeconomic impacts of this policy shock on Northern Nigeria, a region where poverty rates remain high, insecurity is structural, and adaptive capacity is low. Using a qualitative methodology, data will be collected through key informant interviews, community discussions, and textual analysis of official reports and socioeconomic data. Employing a social vulnerability framework, the analysis will examine how subsidy removal exacerbated social inequality and reshaped survival strategies. The findings will show that economic hardship was particularly severe for lower classes, people in the informal economy, and those in villages, resulting in reduced purchasing power, food insecurity, and social stress. Conflict zones and socioeconomically disadvantaged areas of Northern Nigeria were especially affected where social welfare programmes are clearly lacking or absent. The thesis argues that the sudden removal of subsidies, without any social welfare programme in place, increases social vulnerability and undermines the legitimacy of governance. The research concludes by recommending a new approach to subsidy reform, involving phased implementation, targeted support, and region-specific adaptation, to mitigate negative socioeconomic impacts and restore the legitimacy of state–citizen relations.